Respuesta :
Answer:
[tex]3x^{3} -25x^{2} -44x+10[/tex]
Step-by-step explanation:
Hello!
To solve this we distribute what in one parenthesis into the other
3x
3x * x^2 = 3x^3
3x * -10x = -30x^2
3x * 2 = 6x
5
5 * x^2 = 5x^2
5 * -10x = -50x
5 * 2 = 10
Now we put like terms together and simplify
3x^3 + 0 = 3x^3
-30x^2 + 5x^2 = 25x^2
6x - 50x = -44x
0 + 10 = 10
Put it all together
3x^3 + 25x^2 - 44x + 10
Hope this helps!
Answer:
3x^3 + 25x^2 - 44x +10
Step-by-step explanation:
To answer this use FOIL
First Outer Inner Last
In this problem start by distributing the 3x
3x^3-30x^2+6x
Next distribute the 5 in the second parenthesis
5x^2 - 50x + 10
Lastly, add like terms (terms that have the same variable and powers)
3x^3 - 25x^2 +6x +10